Referendums : a comparative study of practice and theory - Butler, David; Ranney, Austin (Washington : American Enterprise Institute for Public Policy Research, 1978)
The books deals with the increasing use of popular referendums in several nations around the world to express widespread and growing dissatisfaction with the responsiveness and sagacity of elected representatives.
Bibliography: p. 247-248.
obn 25/01/2019
Loans
Keywords: Referendum; Comparative government